Design and characterization of multiple coupled microring based wavelegnth demultiplexer in silicon-on-insulator (SOI) - Haroon, Hazura; Abdul Razak, Hanim; Bidin, Mardiana; Menon, P Susthitha; Shaari, Sahbudin; Arsad, Norhana; Mukhtar, ‪Wan Maisarah; Abdullah, Huda (World Scientific Publishing Co Pte Ltd, 2012)
We report in this paper, an optimized design and characterization of SOI based single mode, four channels wavelength demultiplexer using microrings. The usage of siliconon-insulator (SOI) allows a wide free spectral range (FSR) for the device that is crucial in developing ultra-compact integrations of planar lightwave circuits (PLCs). The characterizations are done using Finite-Difference Time-Domain (FDTD) mode simulations from RSOFT. Serially cascaded microring arrays up to the third order are presented to study the design trade-off among the FSR, Q-factor and optical losses of the laterally coupled wavelength demultiplexer. The demultiplexer is expected to be working at C-band region of Wavelength Division Multilplexing (WDM) for a wavelength around 1550 nm. Our proposed demultiplexer has low insertion loss (< 0.5 dB) and a crosstalk around 12 ∼ 19 dB.